To the Castle! A comparison of two audio guides to enable public discovery of historical events - Fitzgerald, Elizabeth; Taylor, Claire; Craven, Michael P. (Springer, 2013)
This paper describes and compares two audio guides used to inform the general public about local historical events, specifically the 1831 Reform Riot as it happened in and around Nottingham in the UK. One audio guide consisted of a guided walk, organised and produced by a local community history group, where members of the group performed spoken narratives at specific points of interest around Nottingham city centre, delivered to a large group of participants. The other guide was a trail of geolocated audio files, created by the same community history group and delivered via location-aware smartphones to a smaller group of participants. This second guide provided similar historical information at the same points of interest as the guided walk, authored using a third party software app that employed a mapping facility to trigger audio events at specified locations. Our central research question was to examine how these experiences differed, or were similar; whether they provided an effective means of learning by the general public about local historical events; and how these kinds of techniques can be used in the future or by other community groups.